Actual spreading and future evolution of alien population of Coypus (Myocastor coypus) in Campania region - Belfiore, Arianna Morena; Troiano, Claudia; Buglione, Maria; Petrelli, Simona; De Filippo, Gabriele; Fulgione, Domenico (BORNH Bulletin of Regional Natural History, 2021)
This study has two main objectives: to define the presence of an alien species, the coypu (Myocastor coypus), in the Campania region and to develop a demographic projection in the absence of management plans. It was possible to highlight the areas in which the species is currently present on the territory and, once the biological and ecological aspects of it have been analysed, to observe whether favourable environmental conditions are present in the Campania region for its survival and proliferation. The results obtained from the environmental suitability model have effectively highlighted the presence of variables that can affect the survival of the species and that the synergy between these can lead to unexpected results. Therefore, to decipher the actual danger of the species it was necessary to develop a demographic projection to observe whether the latter may increase over time. The outcome highlighted an exponential increase in the population over time, thus highlighting the need to intervene in the short term to mitigate the negative impacts that the coypu already perpetuates on the environment.